Effective utilization of climate change trust fund in adaptation programs in Bangladesh: a focus on stakeholder participation - Kabir, Syed Enamul (BRAC University, 2014)
This thesis is submitted in partial fulfillment of the requirements for the degree of Masters of Arts in Governance and Development, 2014.